2014
DOI: 10.1080/03632415.2014.924409
|View full text |Cite
|
Sign up to set email alerts
|

Fish Community Responses to Mechanical Removal of Nonnative Fishes in a Large Southwestern River

Abstract: Establishment of nonnative fishes has contributed to the decline of native fishes worldwide. Efficacy of mechanical removal of nonnative fishes in large streams has been difficult to ascertain, and responses by native fishes after removal is equivocal. We summarize results of efforts on the San Juan River, New Mexico, Colorado, and Utah, to suppress nonnative Channel Catfish and Common Carp densities through removal via electrofishing. We assessed spatial and temporal trends in the densities of abundant fishes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
71
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 37 publications
0
71
0
Order By: Relevance
“…Long-distance movements of Blue Catfish in the Potomac River indicate that robust control measures will be needed to reduce population abundance and minimize negative impacts of this species on the native estuarine community. Attempts to reduce the abundance of nonnative species in other river systems in the USA have yielded varying results due to compensatory responses in nonnative populations and the potential refuges afforded by the connectivity and complexity of large river systems (Coggins et al 2011;Franssen et al 2014;Weber et al 2016). Additionally, nonnative fish removal programs are expensive and require multiple-year efforts before effects are evident.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Long-distance movements of Blue Catfish in the Potomac River indicate that robust control measures will be needed to reduce population abundance and minimize negative impacts of this species on the native estuarine community. Attempts to reduce the abundance of nonnative species in other river systems in the USA have yielded varying results due to compensatory responses in nonnative populations and the potential refuges afforded by the connectivity and complexity of large river systems (Coggins et al 2011;Franssen et al 2014;Weber et al 2016). Additionally, nonnative fish removal programs are expensive and require multiple-year efforts before effects are evident.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Results showed that the fish would be killed if they remained exposed to the same power level for longer than 15 seconds [7]. Franssen and colleagues were partially successful in their use of electric fish capture methods in the San Juan River, New Mexico, and Utah to reduce (or eliminate) the density of the non-native species of fish [8]. Parker and colleagues examined the efficiency of the electric barrier system implemented in the Chicago Sanitary and Ship Canal on some fish species by increasing electrical output value; the results showed that the barrier worked [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive and continued use of nonnative removal efforts, there has been limited documented success in these systems (Mueller ), largely due to the difficulty in linking population changes to these management actions over large spatial and temporal scales (Franssen et al. ; Propst et al. ).…”
mentioning
confidence: 99%
“…Mechanical removal of nonnative fishes in the San Juan River, New Mexico and Utah, has been ongoing since the late 1990s, with variable effort and spatial coverage, to aid endangered fishes (Franssen et al. ). Removal efforts have focused primarily on Channel Catfish Ictalurus punctatus and Common Carp Cyprinus carpio , with the latter being effectively reduced in number over time; however, Channel Catfish remain relatively abundant in the system (Franssen et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation